Pengaruh Efektivitas SIA, Kecanggihan Teknologi Informasi, dan Kemampuan Teknik Pemakai SIA pada Kinerja Individu - Dewi, Luh Putu Radhakrishnan; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
The purpose of this study is to obtain empirical evidence regarding the effect of the effectiveness of accounting information systems, the sophistication of information technology, and the technical ability users of accounting information systems of individual performance. This research was conducted on 27 BPR in Gianyar Regency. The number of samples taken is 108 respondents with the method of determining the sample, namely the saturated sample method. Data collection is done by distributing questionnaires, documentation and interviews. The data analysis technique used is multiple linear regression analysis techniques. The results of this study indicate that the effectiveness of accounting information systems, the sophistication of information technology, and the technical ability users of accounting information systems have a positive effect of individual performance. Keywords : Effectiveness AIS, sophistication IT, technical ability users AIS, individual performance.